Does Ankle Muscle Performance Mirror Improved Pain Following Total Ankle Arthroplasty?. Issue 3 (14th September 2018) - DiLiberto, Frank; Haddad, Steven; Thompson, Julia; Vora, Anand
Category: Ankle Arthritis Introduction/Purpose: Total ankle arthroplasty (TAA) outcomes include pain reduction and improved gait speed. Ankle push off power, which requires gastroc-soleus muscle strength, is a critical aspect of healthy gait and increases as gait speed increases. It appears that improvements in pain translate to improved ankle muscle performance. However, ankle power after TAA is surprisingly low. It is possible years of arthritis and latent muscle memory result in reduced gastroc-soleus muscle strength and a gait pattern reliant on proximal joints for power. Evaluating these hypotheses will drive postoperative care. The purpose of this ongoing prospective study is to be the first to evaluate the interplay of pain, gait speed, and ankle muscle performance (strength and power) in people following TAA for end-stage ankle arthritis. Methods: Twelve people [Mean (SD): Age 61 (14.3) years; BMI 30.0 (5.4) Kg/m2; 83% male] with end-stage ankle arthritis who were candidates for TAA participated (12 preoperative and 9 six-month postoperative visits). Performance of adjunct soft tissue procedures and postoperative care were patient specific. A twenty point numeric pain rating scale was used to measure worst pain in the past week. Three dimensional multi-segment foot motion analysis was performed while participants walked barefoot on level ground over a force plate. Ankle peak push-off power (joint torque x segmental velocity) was calculated. Ankle peak isokinetic plantarflexion strength (torque at 60 degrees / second) and ankle sagittal plane passive range of motion were measured with a dynamometer. Participants also completed the six minute walk test. Wilcoxon Signed Rank tests were used to evaluate preoperative to postoperative changes and between limb differences postoperatively. Results: Pain decreased (postoperative mean = 2.8; p = 0.01) and gait speed increased following TAA (p = 0.02). Ankle plantarflexion strength and ankle power during walking were preserved following TAA (both p > 0.8) (Figure 1). Postoperative group mean dorsiflexion was 25.1 degrees and plantarflexion was 18.9 degrees, suggesting sufficient ankle motion was present for plantarflexor muscle performance. However, between limb differences were significant for both strength and power (both p < 0.05) postoperatively. The involved ankle produced 36% less strength and generated 45% less power during walking in comparison to the uninvolved limb. This asymmetry demonstrates that involved limb ankle muscle performance was not normalized at six-month follow up, despite improvements in pain. Conclusion: Study findings provide preliminary evidence that improved pain and gait speed are disconnected from ankle muscle performance following TAA. Postoperative improvements in gait speed were likely driven by more proximal joints (i.e. hip). Without additional targeted postoperative plantarflexion strengthening and gait training to improve ankle muscle involvement, gains in ankle power, a symmetrical gait pattern, and patient tolerance to higher level activity (i.e. stairs) are unlikely to occur long-term. The underpinning mechanisms limiting the necessary strength to drive power generation (i.e. length-tension relationship, atrophy), and the possible cumulative effect of how abnormal gait may influence implant survivorship deserve further attention.